Nonlocal Approach to CAFE Solution of Creep Crack Growth Problem - NOWAK, Krzysztof (Engineering Transactions, 2016)
Solving a creep crack growth problem using the CAFE methodology encounters the problems typical of other local methods. This article presents a nonlocal grid method applied in order to regularize these problems. The subject of the analysis is a rectangular plate with a central hole and an internal crack. The results obtained for different mesh sizes have subsequently been compared.